Effect of load models and voltage step constraint on distributed generation operated at unity and variable power factors - Payasi R.P.; Singh A.K.; Singh D. (My University, 2025)
The optimum location and size of distributed generation (DG) are affected with many factors. Some important factors, which must be considered in distributed generation planning (DGP), are load model, seasonal variations in load, and voltage step constraint. In previous works, the load model and voltage step constraint are considered separately by different authors. Further, the effect of voltage step on size of DG has been considered for fixed locations and particular operating power factor of DG. In this paper, the voltage step constraint, load model, and seasonal variations in load are considered together. An investigation into optimal location, size, and power factor of DG considering voltage step constraint and mixed load model is performed. The types of DGs capable of delivering real power as well as capable of delivering both real and reactive power are compared. The investigation shows that voltage step constraint is more effective for constant power load model, and the optimum size of DG may also increase with optimum location, instead of decrease. © 2012 Praise Worthy Prize S.r.l. - All rights reserved.